Effect of Contaminants on the Gas Holdup and Mixing in Internal Airlift Reactors Equipped with Microbubble Generator - Surya K. Pallapothu; Adel M. Al Taweel (International Journal of Chemical Engineering, 2012)
The impact of contaminants on the gas holdup and mixing characteristics encountered in internal airlift reactors was investigated using a 200 L pilot scale unit equipped with a two-phase transonic sparger capable of generating microbubbles. Small dosages of a cationic surfactant (0–50 ppm of sodium dodecyl sulfonate (SDS)) were used to simulate the coalescence-retarding effect encountered in most industrial streams and resulted in the formation of bubbles that varied in size between 280 and 1,900 μm. Gas holdups as high as 0.14 were achieved in the riser under homogeneous flow regime when slowly coalescent systems were aerated at the relatively low superficial velocity of 0.02 ms−1, whereas liquid circulation velocities as high as 1.3 ms−1 were achieved in conjunction with rapidly coalescent systems at the same superficial velocity. This excellent hydrodynamic performance represents a 5-fold improvement in the riser gas holdup and up to 8-fold enhancement in the liquid circulation velocity and is expected to yield good mixing and mass transfer performance at low energy dissipation rates.